2020
DOI: 10.1101/2020.07.12.199737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cyanate – a low abundant but actively cycled nitrogen compound in soil

Abstract: Cyanate (NCO-) can serve as a nitrogen and/or carbon source for different microorganisms and even additionally as an energy source for autotrophic ammonia oxidizers. Despite the widely distributed genetic potential for direct cyanate utilization among bacteria, archaea and fungi, the availability and environmental significance of cyanate is largely unknown, especially in terrestrial ecosystems. We found relatively low concentrations of soil cyanate, but its turnover was rapid. Contrary to our expectations, cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The gene coding for cyanate lyase was also enriched in [ 11 C]CH 4 uptake hotspots. Cyanate lyase catalyses cyanate transformation to carbamate, which may convert to NH 3 and CO 2 (Johnson & Anderson, 1987; Mooshammer et al, 2021). While this may be an important NH 3 source for microorganisms, low concentrations of cyanate (≈pmol g −1 soil) and its transient nature (Mooshammer et al, 2021) preclude use of N‐XANES for identification in soils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene coding for cyanate lyase was also enriched in [ 11 C]CH 4 uptake hotspots. Cyanate lyase catalyses cyanate transformation to carbamate, which may convert to NH 3 and CO 2 (Johnson & Anderson, 1987; Mooshammer et al, 2021). While this may be an important NH 3 source for microorganisms, low concentrations of cyanate (≈pmol g −1 soil) and its transient nature (Mooshammer et al, 2021) preclude use of N‐XANES for identification in soils.…”
Section: Resultsmentioning
confidence: 99%
“…Several CH 4 metabolism-related genes detected within R. (Johnson & Anderson, 1987;Mooshammer et al, 2021). While this may be an important NH 3 source for microorganisms, low concentrations of cyanate (≈pmol g −1 soil) and its transient nature (Mooshammer et al, 2021) preclude use of N-XANES for identification in soils. N-limited environments (Bodelier & Laanbroek, 2004;Mohanty et al, 2006).…”
Section: Positron-emitting Radiotracers Spatially Resolve Taxonomic A...mentioning
confidence: 99%
“…Previous studies primarily addressed cyanate utilization, the sources of cyanate largely unknown (Kitzinger et al, 2019;Linder, 2019;Saéz et al, 2019;Mooshammer et al, 2021). The results of this study reveal that cyanate can be produced by photochemical degradation of DOM in diverse environments.…”
Section: Disparities In Sources and Composition Of Dom In Various Env...mentioning
confidence: 88%
“…Cyanate also serves as an organic nitrogen source in both terrestrial and marine environments. It is recently found that cyanate serves as an active nitrogen or energy source for soil microbes (Mooshammer et al, 2021). The discovery of the cyanase gene in various marine microbes, particularly in the picocyanobacterial strains, such as Synechococcus sp.…”
Section: Introductionmentioning
confidence: 99%